Selective oxidative stress induces dual damage to telomeres and mitochondria in human T cells. Issue 12 (9th November 2021) - Wang, Ling; Lu, Zeyuan; Zhao, Juan; Schank, Madison; Cao, Dechao; Dang, Xindi; Nguyen, Lam Nhat; Nguyen, Lam Ngoc Thao; Khanal, Sushant; Zhang, Jinyu; Wu, Xiao Y.; El Gazzar, Mohamed; et al.
Abstract: Oxidative stress caused by excess reactive oxygen species (ROS) accelerates telomere erosion and mitochondrial injury, leading to impaired cellular functions and cell death. Whether oxidative stress‐mediated telomere erosion induces mitochondrial injury, or vice versa, in human T cells—the major effectors of host adaptive immunity against infection and malignancy—is poorly understood due to the pleiotropic effects of ROS. Here we employed a novel chemoptogenetic tool that selectively produces a single oxygen ( 1 O2 ) only at telomeres or mitochondria in Jurkat T cells. We found that targeted 1 O2 production at telomeres triggered not only telomeric DNA damage but also mitochondrial dysfunction, resulting in T cell apoptotic death. Conversely, targeted 1 O2 formation at mitochondria induced not only mitochondrial injury but also telomeric DNA damage, leading to cellular crisis and apoptosis. Targeted oxidative stress at either telomeres or mitochondria increased ROS production, whereas blocking ROS formation during oxidative stress reversed the telomeric injury, mitochondrial dysfunction, and cellular apoptosis. Notably, the X‐ray repair cross‐complementing protein 1 (XRCC1) in the base excision repair (BER) pathway and multiple mitochondrial proteins in other cellular pathways were dysregulated by the targeted oxidative stress. By confining singlet 1 O2 formation to a single organelle, this study suggests that oxidative stress induces dual injury in T cells via crosstalk between telomeres and mitochondria. Further identification of these oxidation pathways may offer a novel approach to preserve mitochondrial functions, protect telomere integrity, and maintain T cell survival, which can be exploited to combat various immune aging‐associated diseases. Abstract : Oxidative stress caused by excess reactive oxygen species (ROS) accelerates telomere erosion and mitochondrial injury, leading to impaired cellular functions and cell death. By selectively producing singlet 1 O2 to a single organelle, Wang and Lu et al. demonstrate that oxidative stress induces dual injury in T cells via crosstalk between telomeres and mitochondria, and also explore potential molecules and pathways that promote this dual‐damage.